Government financial support and financial performance of SMEs: a dual sequential mediator approach - Jayeola, Olakunle; Sidek, Shafie; Sanyal, Shouvik; Hasan, Syed Inamul; An, Nguyen Binh; Mofoluwa Ajibade, Samuel-Soma; Phan, Thi Thu Hien (Elsevier BV, 2022)
Government financial support (GFS) is an important factor for firms in developing countries, particularly small and medium enterprises (SMEs), to be competitive and perform better. Nonetheless, studies on the relationship between GFS and firm performance have yielded inconclusive results. Researchers' efforts to resolve the inconclusiveness led to an examination of competitive advantage (CA) as a simple mediator. This study contends that CA should not be the first mediator but rather a resource acquired with GFS, such as cloud ERP, which has CA-enabled qualities, as opposed to GFS, which lacks the ability to offer CA to firms. Hence, using 204 Malaysian manufacturing SMEs as a sample, this study investigates the dual sequential mediation of cloud ERP implementation (CERPI) and CA in the GFS-financial performance (FPER) relationship. PLS-SEM was employed as a data analysis method and for hypotheses assessment. Findings reveal that the GFS is not directly associated with FPER. However, GFS is positively related to CERPI, which subsequently enhances CA positively. CA is also positively associated with FPER, and CERPI and CA sequentially mediate the GFS and FPER relationship positively. This study makes a contribution to the literature by providing a more holistic understanding of the complex relationship between GFS and FPER. This study could assist SMEs and policymakers in gaining a better understanding of the process and requirements for realising valuable benefits from GFS.